Need for patient education and better physician-patient communication in melanoma patients: Behaviors and knowledge of melanoma patients - Sezgi Sarıkaya Solak; Haydar Yöndem; İrfan Çiçin (Galenos Publishing House, 2021)
Background and Design: Melanoma is a serious type of cancer. Patients previously diagnosed with melanoma are at an increased risk of a second melanoma. Therefore, it is important to know and apply preventive measures. This study aimed to examine melanoma patients' behaviors of sun protection and skin self-examination (SSE), knowledge on risk factors, and communication with their physicians about the disease. Materials and Methods: A questionnaire-based cross-sectional study was conducted in 65 melanoma patients to assess knowledge of melanoma and sun protection and determine SSE attitudes and patient-physician communication. Results: Sun exposure was a well-known melanoma risk factor (67.7%), but the knowledge level on other risk factors, especially regarding skin, hair, and eye color phenotypes, was low (between, 21.5% and 36.9%). Sunscreen use practice was insufficient (33.8%) and mostly inadequate. The most commonly reported reason for not using sunscreen was not having a habit of sunscreen use (83.7%). Compliance with other sun protection behaviors was variable. Half (50.8%) of the melanoma patients reported that they perform SSE. The most commonly reported reasons for not performing SSE was not knowing its necessity (71.8%). More than one-third (35%) of patients stated that they did not receive information about melanoma from their physicians. Almost all patients who received information from their physicians were informed verbally, and only 4% received written information. Conclusion: Our study highlights the need for a comprehensive education for patients about all aspects of melanoma and strategies to improve patient-physician communication. Barriers to preventive behaviors in melanoma patients may be determined in more detail in larger future studies and the content of education may be planned accordingly.